Mapping of the fallow land using Landsat imageries for utilization of cropping area in Tamil Nadu, India - SRINIVASAN, R.; RAMAMURTHY, V. (Journal of Soil and Water Conservation, 2025)
A prospective piece of land that has been left fallow is one that has not been used for crop production or any other purpose. Leaving land fallow for an extended period lowers crop productivity and soil quality. Quantification and assessment of fallow lands are crucial for the sustainable development of the state. The temporal distribution of fallow land is not well understood in Tamil Nadu. To close this knowledge gap, we used Landsat remote sensing data to map crop land and determine the spatial-temporal distribution of fallow land in Tamil Nadu. Tamil Nadu has seen a fluctuation in the distribution of current fallow land from 13.88 to 18.05% over the years. The permanent fallow land has been comparatively stable with a decreasing tendency over time despite fluctuations in the current fallow. The amount of permanent fallow land in the western zone declined from 1,89,904 ha in 2005-2010 to 1,47,011 ha in 2010-2015, and it has slightly increasing trends in 2015-2020. Among all the western zone districts, Tiruppur district has contributed maximum. The southern zone is the main source of permanent fallow land, contributing 5,75,459 ha (4.33%) between 2005 and 2010, 5,79,239 ha (4.36%) between 2010 and 2015, and 6,02,993 ha (4.54%) between 2015 and 2020, respectively. Despite the area appearing to be stable, it is rising slowly and persistently. Southern districts of Madurai and Pudukkottai in this region have significantly reduced the amount of permanent fallow land. While, Ramanathapuram, Thoothukudi, and Virudhunagar districts have all experienced steady growth. Different fallow land assessments aid in the formulation of policies on crop planning and livelihood improvement.